Dampak Komunikasi Digital: Analisis Media Konvensional Ditaklukkan Media Baru Dikalangan Mahasiswa Ilmu Hubungan Internasional Universitas Almuslim - Azhar, Al; Iskandar, Umar (LPPM Universitas Almuslim, 2024)
Media has undergone many changes, from the existence of traditional media, through media convergence to the emergence of new media today. Along with the increasing complexity of technology and the easier access to new media, traditional media is slowly being eliminated from the market. Students are actively using digital media. What are the differences in the use of traditional media and new media among students of the International Relations Study Programme, Faculty of Social and Political Sciences, Almuslim University. Then, what are the responses and critical reactions that students have to communication in the current digital era? The purpose of this study is to determine the differences in the use of traditional communication media and new communication media among students of the International Relations Study Program class of 2024. The research methodology used in this study is a qualitative methodology that involves descriptive description through data analysis techniques in the form of interviews and field surveys (observation). The findings of this study indicate that the emergence of new media in today's digital era has both positive and negative impacts.